A Insuficiência da ordem: discursos e reformas policiais (Fortaleza 1930-1945) - Gonçalves, Daniel da Costa (2011)
The point of view that guides this work is a discourse analysis on reforms applied to the police force in the city of Fortaleza, State of Ceara, during the Vargas Era (1930-1945). The analysis is based on main sources from local newspapers, the Revista Policial (The Police Magazine) and Reports from Police Chiefs, which are discursive instances for the buildup of legitimacy and credibility involving the police institution in its reforming quest for production of social order. Reforms of the police structure that took place during this period, highlighted by construction of the Palacio da Policia Central (Palace of Central Police) were part of a practical attempt aiming at establishing an order that had been claimed by downtown stores, catholic conservative priests and “highly placed public servants” attached to the police force. The world of order and lawlessness was nominated, classified and invented as a discourse that propounded presence and absence of police. The historical unfolding of this process is full of misunderstandings, tensions, breaking of deadlines and inadequacies of an order based on investments by the State involving reforms to the police-technical apparatus aimed at social control of the city and its population. Since then, in Fortaleza, social order is misapprehended as “police-controlled society”.